Boundary optimization and coercivity enhancement of high (BH)max Nd-Fe-B magnet by diffusing Pr-Tb-Cu-Al alloys. (September 2017) - Lu, Kechao; Bao, Xiaoqian; Tang, Minghui; Chen, Guixian; Mu, Xing; Li, Jiheng; Gao, Xuexu
Abstract: Commercial N50 Nd-Fe-B magnet was processed by grain boundary diffusing Pr-Tb-Cu-Al alloys. The coercivity increased from original 944.9 kA/m to 1640.6 kA/m, 1741.6 kA/m, 1740.2 kA/m and 1775.4 kA/m by diffusing Tb70 Cu30, Pr52.5 Tb17.5 Cu30, Pr60 Tb20 Al20 and Pr60 Tb10 Cu15 Al15 alloys, respectively. Microstructural analysis confirmed Tb-rich shells on the surfaces of Nd2 Fe14 B grains, contributing to coercivity enhancement of diffused sample. Especially, the partial replacement of Tb by Pr in diffusion sources resulted in higher coercivity by consuming fewer Tb elements, only 0.34–0.53 wt% Tb in the sample by Pr-Tb-Cu-Al, much lower than 1.82 wt% Tb in the sample by Tb-Cu. Graphical abstract: